Positional Differences of the Mandibular Canal in Relation to Permanent Mandibular First Molars with Eruption Disturbances in Children - Eungyung Lee; Taesung Jeong; Jonghyun Shin (MDPI AG, 2020)
Eruption disturbances in permanent mandibular first molars (PM1s) are uncommon. This retrospective study aimed to investigate differences in the position of the mandibular canal in relation to PM1s, with or without, eruption disturbances. Panoramic and cross-sectional views were reconstructed from cone-beam computed tomography imaging of children with PM1 eruption disturbances. Distances from the most inferior margin of the mandible to the center of the mandibular canal (M-C) and from the outer margin of the lingual cortex to the center of the mandibular canal (L-C) were measured for normally erupted PM1s (normal group) and for PM1s with eruption disturbances (ED group) and compared using independent t-tests. The mean M-C was significantly shorter in the ED group (4.86 ± 1.07 mm) than in the normal group (6.56 ± 1.06 mm) (p < 0.05). The mean L-C was also significantly shorter in the ED group (2.74 ± 0.74 mm) than in the normal group (3.09 ± 0.71 mm) (p < 0.05). This study demonstrated that the mandibular canal tended to be positioned more inferiorly in relation to PM1s with eruption disturbances than normally erupted PM1s in children. Clinicians should be aware of this positional deviation when managing children with PM1 eruption disturbances.